The Role and Advantages of the Digital Economy in the Establishment of "New Uzbekistan" - Umarova Hulkar Umidulloyevna (International Journal on Orange Technologies, 2023)
In this article, the new reforms carried out in our republic, the directions of the "Strategy of Development" in the establishment of the New Uzbekistan, the transformation of the digital economy into the main driving sector in the rapid development of the national economy, the use of digital technologies, the analysis of their possibilities, in all sectors of the economy works based on the introduction of digital technologies have been identified. Also, by studying, systematizing and summarizing the existing practice in drawing up scientifically based conclusions on the introduction of the digital economy, suggestions are made not only on how it will take an important place in the economy and in what form it will be introduced.